1968
DOI: 10.1109/tap.1968.1139244
|View full text |Cite
|
Sign up to set email alerts
|

Very high frequency radiowave scattering by a disturbed sea surface Part II: Scattering from an actual sea surface

Abstract: A two-scale model of rough surfaces is considered which permits theoretical interpretation of the features of very high frequency scattering from such surfaces (say, from a sea surface). The scattering snrface is a m e d to be a superposition of small-scale ripple and large waves (swell). Reflection from the latter may be considered by the Kirchhoff approximation. The spatial spectrum of corrugations is taken into consideration; the calculations based on this model help to give an explanation of the behavior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(92 citation statements)
references
References 23 publications
5
86
0
Order By: Relevance
“…Specifically, the measured one-dimensional frequency spectra show a slope which increases from w-4 to near w- 5 at the higher wavenumbers. This agrees with the DHH spectral model at the low frequency end, but behaves much more like earlier models predicting the steeper slope of -5.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Specifically, the measured one-dimensional frequency spectra show a slope which increases from w-4 to near w- 5 at the higher wavenumbers. This agrees with the DHH spectral model at the low frequency end, but behaves much more like earlier models predicting the steeper slope of -5.…”
Section: Discussionmentioning
confidence: 93%
“…Research in the 1960's showed that these limitations could be overcome if the 'slightly rough surfaces' theory was further modified by assuming that the large scale waves on the sea surface could be broken into small patches of tangent planes upon which the shorter scale scatterers propagated [4,5,69]. The perturbation theory, therefore, is applied to individual small patches that are summed to get the total scattered return, assuming that the short waves decorrelate very quickly relative to the large scale waves.…”
Section: General Theoretical Developmentmentioning
confidence: 99%
“…This deterministic integration is well suit for the extension to local facet frame. However, they only gave the monostatic scattering formula with application to Gaussian distribution seas [17,18]. And, withal, in our opinion, their model still has poor performance in the specular zone.…”
Section: Introductionmentioning
confidence: 87%
“…2. According to the two scale scattering model presented by Bass and Fuks [12,17,18], we get the scattering field in case of a dielectric rough surface and a plane incident wave.…”
Section: Bistatic Investigation On Bass-fuks Two Scale Model (Bftsm)mentioning
confidence: 99%
“…The second-order small perturbation method (SPM) [15][16][17] can predict the depolarized scattering in and out the plane of incidence, but its validity domain is restricted to the small roughness cases. The two scale model (TSM) [18][19][20][21] also known as composite surface model underestimates the cross-polarized components due to the neglect of second-order Bragg scattering. In comparison with the classical model such as SPM, KA and TSM, the modern analytical approximate model of second-order small-slope approximation (SSA-II) takes into account the mutual transformation of the two linear polarization states caused by facets tilts as well as the second-order Bragg scattering [22], and thus can predict the depolarized scattering from rough sea surface both in and outside the plane of incidence.…”
Section: Introductionmentioning
confidence: 99%